The cave crickets of the genus Dolichopoda from Evvia and Skyros islands: formal description of D. octhoniai and D. saraolacosi (Orthoptera: Rhaphidophoridae) - Alexiou, Sotiris; Di Russo, Claudio; Rampini, Mauro (Fragmenta entomologica, 2015)
Two species, D. octhoniai from Evvia and D. saraolacosi from Skyros island (Greece) are morphologically described. These two species were collected for the first time at the end of the ‘70s but they were recorded only as nomina nuda without any formal taxonomic description. D. octhoniai is very similar to the other Evvian species D. makrikapa and to D. vandeli and D. petrochilosi from Viotia and Attiki respectively, differing from them only by a few morphological characters. On the other hand D. saraolacosi is very different from all the other species of Central Greece and West Aegean showing some affinity only with the Attiki species D. insignis and with the South Evvian species D. cassagnaui. Relationships among the species inhabiting caves of this area of Greece are discussed in relation to the complex geological history of the West Aegean area and the adjacent mainland.